Penguatan Praktik Pemberian Makanan pada Bayi dan Anak (PMBA) Melalui Simulasi dan Demonstrasi Pemberian MP-ASI - Yudianti Yudianti; Hapzah Hapzah; Nurliah Nurliah; Nurbaya Nurbaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
West Sulawesi Province is the highest province with stunting above the WHO cut-off (20%), where the incidence of stunting in West Sulawesi is 39.7%. One of the causes of growth and development disorders for babies and children aged 6 to 23 months in Indonesia is the low level of knowledge and practice of providing exclusive breastfeeding, the low quality of complementary feeding. This activity aimed to train and strengthen the practice of giving complementary foods to toddlers by simulating and demonstrating giving complementary foods in accordance with WHO standards. The methods used are counseling, simulation and demonstration of complementary feeding patterns. The target was 30 mothers of toddlers and 5 posyandu cadres. There was an increase in participants' knowledge from 60% to 97% and participants were able to demonstrate the practice of providing MP-ASI based on local food well. It is important to frequently refresh the pattern of giving complementary foods to mothers in groups so that mothers can share knowledge and support each other in practicing the right pattern of giving complementary foods.